Phytochemical profiling and antioxidant potential of methanolic extract of Vitis vinifera L seeds - Lakshmi, Sindhuja; Padmavathy, Kesavaram; UmaArasu, Thirunavukarasu; Prabu, Dhandapani (Chulalongkorn Medical Journal, 2024)
Background: Grapes are the most widely consumed fruit worldwide. Grape seeds are a natural source of polyphenols that possess pharmacological and therapeutic activities. The grape seeds have long been used in traditional medicine to alleviate various illnesses. Objective: This study aimed to identify the major phytocompounds of grape seed methanolic extract and evaluate its antioxidant activity. Methods: The methanolic extract of grape seeds was subjected to gas chromatography–mass spectrometry to identify the major phytochemical compounds, and further antioxidant activity was evaluated using 2, 2- diphenyl-1-picrylhydrazyl (DPPH) as per the guidelines of the Association of Official Analytical Chemist. Results: In total, 10 phytochemical compounds (1, 3, 5-benzenetriol, 1, 3-benzenediol, benzoic acid, reticuline, 2-hydroxy-5-methylisophthalaldehyde, 4-vinylbenzene-1, 2-diol, cyclohexane carboxylic acid, eicosanoic acid, octadecanoic acid, and 2, 6, 10, 14, 18-pentamethy l - 2, 6, 10, 14, 18-eicosapentaene) were identified in the methanol extract. By the DPPH method, the antioxidant activity of the extract was 212.6 µg/kg. Conclusion: Phytochemical profiling of the methanolic extract of grape seeds revealed the presence of phenols (1,3-benzenediol, 4-vinylbenzene-1,2-diol), polyphenol (1,3,5-benzenetriol), phenolic acid (benzoic acid), alkaloid (reticuline), aldehyde (2-hydroxy-5-methylisophthalaldehyde), straight-chain saturated fatty acid (eicosanoic acid and octadecanoic acid), and carboxylic acid (cyclohexane carboxylic acid). Of these phytocompounds, benzoic acid and reticuline are potent natural antioxidants that would be effective against free radicals/reactive oxygen species with wider therapeutic applications in metabolic disorders, inflammatory conditions, and cancer.